Perawatan Gingivektomi Pada Pasien Enlargement Gingiva - Intan Sari Mahardika; Ariyani Faizah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction: Periodontal tissue is a supporting and protective tissue of the teeth consisting of gingiva, periodontal ligament, cementum, and alveolar bone. One type of periodontal disease is gingival enlargement. The main factor that causes this disease is bacterial plaque, so gingivectomy treatment is needed. Gingivectomy is a procedure to cut excess gingival tissue with the aim of eliminating pockets and gingival inflammation, so that good physiological, functional and aesthetic gingiva is obtained. Case: A 19-year-old male presented to Soelastri Dental and Oral Hospital with complaints of gingival enlargement, which had been occurring for the past six months, primarily affecting the upper right posterior and lower anterior gingiva. The patient reported no history of systemic illness and no known allergies to medications or food. Clinically, the gingiva appeared enlarged, soft in consistency, reddish in color, with blunted gingival margins. Periodontal pocket depths were recorded as follows: tooth 32 : 433, 31 : 423, 41 : 323 and 42 : 333. A diagnosis of gingival enlargement was established.. Management: The initial treatment consisted of scaling and root planing. However, no significant improvement was observed at the 7-day follow-up. Consequently, gingivectomy was performed on teeth 32, 31, 41, and 42. A follow-up evaluation was conducted 10 days post-operatively. Intraoral examination revealed periodontal pocket depths of 31 (2-1-1), 32 (2-1-2), 41 (2-1-2), and 42 (2-1-2). The patient demonstrated good oral hygiene, with a marked reduction in gingival enlargement. Nonetheless, mild edema and erythema persisted on the labial aspect of teeth 41 and 42. Conclusion : Gingival enlargement is an inflammation that occurs in the gingiva due to local factors, namely plaque bacteria. Treatment of gingival enlargement that does not shrink after scaling, root planing, must be performed gingivectomy so that good morphology and aesthetics are obtained.